Online simultaneous determination of lactoferrin and immunoglobulin G in dairy products by two-dimensional liquid chromatography - CHEN Qin; ZHOU Langjun; CHEN Zijing; LIU Mengni; LIN Senyu (Shipin yu jixie)
ObjectiveA method of two-dimensional liquid chromatograohy was established to simultaneously determine the content of lactoferrin and immunoglobulin G in dairy products.MethodsThe pretreated samples were directly injected into the constructed system. Target protein and other effects were separated on a Pharmacia HI-Trap Protein G as the first-dimensional column using a mobile phase consisting of sodium phosphate buffer and glycocoll buffer by gradient elution lactoferrin and immunoglobulin G were separated on a BioCore SEC-300 (4.6 mm×250 mm, 5 μm) as the second-dimensional column using a mobile phase consisting of water and sodium phosphate buffer by gradient elution.ResultsThe results showed that the standard curves of Lactoferrin and Immunoglobulin G were linear with R>0.99. The quantitation limits of Lactoferrin in solid samples was 20 mg/kg while in liquid samples was 13 mg/kg, the recovery rate were 91.0%~107.0% and the RSD were 2.4%~5.3%. The quantitation limits of Immunoglobulin G in solid samples was 34 mg/kg while in liquid samples was 7 mg/kg, the recovery rate were 91.2%~104.0% and the RSD were 2.1%~4.7%.ConclusionThe online two-dimensional liquid chromatography system established in the experiment has the advantages of simple pretreatment, high automation, high analysis efficiency, high accuracy and good repeatability, and is suitable for the determination of lactoferrin and immunoglobulin G in dairy products.